IT Leaders’ Experiences of Resilience during the Pandemic : An Appreciative Inquiry - Pai, Asha Albuquerque; N., Nikhil Pazhoothundathil; Ashok, Lena; Mohammed, Ciraj Ali; Sekaran, Varalakshmi Chandra (Prabandhan: Indian Journal of Management, 2023)
Purpose : The COVID-19 pandemic highlighted that leaders need to have the capacity for resilience. When leaders are confronted with disruptions that are now more of a certainty than a possibility, they must have the ability to bounce back, recover, be agile, and be resilient. Objective : To explore the resilience experiences of leaders in the information technology (IT) industry (both mid-level and senior leaders) during the outbreak of the COVID-19 pandemic, guided by the theory of self-leadership. Method : Qualitative exploratory study using an appreciative inquiry approach based on 19 mid- and senior-level leaders, both men and women, in the IT Industry in India, chosen purposively. The data in the form of in-depth interviews were analyzed thematically. Findings : Participants’ experience of resilience during the pandemic was expressed as a capability of leaders, which is inherent in the IT industry, given its dynamism. Various facets of resilience and its impact were highlighted. Practical Implications : The IT industry disruption is characteristic of the pandemic. Hence, understanding how leaders handled the crisis will help in training and development, talent acquisition, self-development, and a guiding pathway for budding leadership. Resilient leaders can positively impact self-leadership by inspiring individuals to develop self-leadership skills, fostering a culture within their organizations, and increasing team self-efficacy. Originality : The resilience capabilities of the leaders in the IT industry in India has not been explored qualitatively before, especially during the pandemic.